Real-time warning signs of emerging and collapsing Chinese house price bubbles - Xi Chen; Michael Funke (Bank of Finland, Institute for Economies in Transition (BOFIT), 2012)
The recent increase in Chinese house prices has led to concerns that China is vulnerable to asset price shocks. In this paper, we apply recently developed recursive unit root tests to spot the beginning and the end of potential speculative bubbles in Chinese house price cycles. Overall, we find that except for 2009-2010 actual house prices are not significantly disconnected from fundamentals. Thus, the evidence for speculative house price bubbles in China is in general weak.
URN:NBN:fi:bof-201408072163
Keywords: C15; G01; G12; R31; 330; house prices; China; speculative bubbles; recursive unit root tests